Studying Kinematics and Capacity of Tools of Organic Fertilizer Loader - Evgenievich Demin, Evgeny; Ivanovich Pavlov, Pavel; Rafitovich Khakimzyanov, Rustam; Alekseevich Mukhio, Victor; Anatolyevich Protasov, Andrey (International Journal of Engineering and Technology, 2018)
This article discusses the issue of theoretical background of capacity of new load handling tools of continuous loaders for organic fertilizers on the basis of kinematic analysis of their motion. Loader efficiency is estimated by a set of performances the main of which is loading capacity. The loading capacity is determined by design and kinematic parameters of tools. Theoretical determination of capacity is an important scientific task, its solution would permit to substantiate loader parameters for predetermined operation conditions. Kinematic analysis of spiral, vane, shredding screw load handling tools is performed. Capacity of shredding tools is determined as a function of design and operation parameters as well as physicochemical properties of organic fertilizers. The obtained equations take into account motion pattern of tools, kinematic and design parameters as well as physicochemical properties of manure. The capacity depends quadratically on tool diameter. Dependence on other parameters is in fact directly proportional. The influence of tool angular velocity and its forward velocity is related with trigonometric functions of rotation angles during separation and gripping of organic fertilizers.Â Â